1998
DOI: 10.1073/pnas.95.6.2985
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1-induced CCR2B receptor desensitization mediated by the G protein-coupled receptor kinase 2

Abstract: A BSTR ACTMonocyte chemoattractant protein 1 (MCP-1) is a member of the chemokine cytokine family, whose physiological function is mediated by binding to the CCR2 and CCR4 receptors, which are members of the G protein-coupled receptor family. MCP-1 plays a critical role in both activation and migration of leukocytes. Rapid chemokine receptor desensitization is very likely essential for accurate chemotaxis. In this report, we show that MCP-1 binding to the CCR2 receptor in Mono Mac 1 cells promotes the rapid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 40 publications
8
123
2
Order By: Relevance
“…This point was further addressed by analyzing the effect of GRK2 on the activation of ERK by a mutated form of the receptor, CCR2BIX (Franci et al, 1996). This receptor has serine/ threonine residues in the C-terminal tail of the protein mutated to alanines, is poorly phosphorylated by GRK2, and consequently, overexpression of GRK2 does not block CCR2BIX-induced calcium response (Aragay et al, 1998a). In cells transfected with CCR2BIX, CCL2 triggered a marked increase of ERK phosphorylation ( Figure 2B) that was potently impaired by GRK2 (70% inhibition).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This point was further addressed by analyzing the effect of GRK2 on the activation of ERK by a mutated form of the receptor, CCR2BIX (Franci et al, 1996). This receptor has serine/ threonine residues in the C-terminal tail of the protein mutated to alanines, is poorly phosphorylated by GRK2, and consequently, overexpression of GRK2 does not block CCR2BIX-induced calcium response (Aragay et al, 1998a). In cells transfected with CCR2BIX, CCL2 triggered a marked increase of ERK phosphorylation ( Figure 2B) that was potently impaired by GRK2 (70% inhibition).…”
Section: Resultsmentioning
confidence: 98%
“…In previous studies, we have analyzed the pathway of activation of MAPKs by CCL2 in monocytes and HEK293-CCR2B cells, which involves heterotrimeric G proteins, protein kinase C, phosphoinositide 3-kinase, and Ras (Aragay et al, 1998a;Jiménez-Sainz et al, 2003). We have also reported that activation of CCR2B by CCL2 leads to its rapid phosphorylation by GRK2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of the receptors in response to agonist stimulation appears to be a key step in termination of the receptor/G protein coupling, which results in desensitization of the receptors (4,7,8). Receptor phosphorylation may also play a role in facilitating certain chemokine receptor internalization (4).…”
Section: Discussionmentioning
confidence: 99%
“…Like other members of the GPCR superfamily, the functional status of many chemokine receptors is determined largely by the phosphorylation state (4 -6). Agonist treatment enhances phosphorylation of the receptors by protein kinases, presumably G protein-coupled receptor kinases and protein kinase C, which results in desensitization of the receptors (4,7,8). This phenomenon is common to many hormonal and neurotransmitter signaling systems (9), but the underlying mechanisms are still only partially understood, especially in the case of chemokine receptors.…”
mentioning
confidence: 99%